Komunikasi Persuasif Petugas Sensus Badan Pusat Statistik Kabupaten Tangerang Dalam Melaksanakan Sensus Penduduk Registrasi Sosial Ekonomi - Rahmaddan, Muhammad Kevin; Saputra, Faisal Tomi; Alamsyah, Alamsyah (Social Science Academic, 2023)
Communications is very important and must be mastered properly by workers working in the field, such as for example population census officers. When working on conducting censuses, census officers were usually trained in job training beforehand. The aim is none other than, so that census workers understand what they have to do in the field, and what has to be conveyed or explained when they are dealing with the public. Because the image or reputation of the Central Bureau of Statistics as the pioneer or executor of the Population Census is tested or at stake there. This study aims to find out how the Persuasive Communication of census officers at the Central Bureau of Statistics of Tangerang Regency in carrying out social and economic registration censuses in Tangerang Regency, especially in Balaraja District. The research method used is a qualitative research method with data collection methods namely Observation, Interview and Documentation. Interviews were conducted with the Kecamatan Sector Coordinator and some of the census officers themselves. The results of this study are the stages of the persuasive communication process in an effort to find out the communication process of census officers in conducting data collection in the field to the community. In addition, objections that become obstacles for census officials are usually objections made by the public based on distrust of the government or fear that the data will be misused by the Central Bureau of Statistics. Therefore, census officers must be able to anticipate or have their own way of overcoming obstacles or resistance by the community during the social and economic registration census data collection process. maximum and the data obtained will also be maximized, of course.